Friday

July 25, 2014

July 25, 2014

Posted by **Marissa** on Sunday, August 12, 2007 at 11:09pm.

answer=-4,1/5

2)Which quadratic equation has roots 7 and -2/3?

answer=A

A.2x^2-11x-21=0

B.3x^2-19x-14=0

C.3x^2+23x+14=0

D.2x^2+11x-21=0

3)To solve 4x^2-28x+49=25 by using the square root property,you would first rewrite the equation as

answer=(2x-7)^2=25

4)Find the value of c that makes x^2+5x+c a perfect square trinomial.

answer=25/4

5)The quadratic equation x^2-8x=-20 is to be solved by completing the square.Which equation would be a step in that solution?

answer=x^2-8x+16=-20

1)Solve by factoring:5x^2=4-19x

answer=-4,1/5

2)Which quadratic equation has roots 7 and -2/3?

answer=A

A.2x^2-11x-21=0

B.3x^2-19x-14=0

C.3x^2+23x+14=0

D.2x^2+11x-21=0

3)To solve 4x^2-28x+49=25 by using the square root property,you would first rewrite the equation as

answer=(2x-7)^2=25

4)Find the value of c that makes x^2+5x+c a perfect square trinomial.

answer=25/4

5)The quadratic equation x^2-8x=-20 is to be solved by completing the square.Which equation would be a step in that solution?

answer=x^2-8x+16=-20

- Algebra -
**Anonymous,**, Thursday, August 28, 2008 at 12:10amcorection is for number 2 is b

**Related Questions**

algebra - 1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic ...

Math - Solve the polynomial equation, to obtain the first root. x^3+7x^2+19x+13 ...

Pre Algebra - Please help me with some problems. Thank you! Solve the equation ...

Math - Hi everyone. Would someone be able to help me with this problems? I know ...

Math - Can anyone help work these problumns out step by step? 11x-37=x+23 10p-26...

math - How to solve this quadratic equation by factoring? 10x2 - 19x -15 = 0

need help - Factor Completely (x-4(x^2+3) Perform the indicated operations (-(...

algebra - 1)Simplify:(6x^3-16x^2+11x-5)/(3x-2) answer= 2x^2-4x+1-3over3x-2 2)...

Algebra - I have a few questions that I need help with. Solve the radical ...

Algebra - Solve the following system of linear equations: 2x - 3y + 6z = -12 5x...